2016
DOI: 10.1080/21681805.2016.1249515
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of bilateral synchronous spermatocytic tumours in a young man seeking fertility preservation

Abstract: Spermatocytic tumours are a rare form of testicular germ cell tumour that normally present in older men. This report presents a case of bilateral spermatocytic tumours in a 25-year-old man. The potential preservation of gonadal function, i.e. fertility and androgen production, is discussed, although this was not possible in this case. Although spermatocytic tumours are considered rare, the tumour is more common than previously thought and presents equally in older and younger men. In cases of bilateral present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Two case reports of PO in a solitary testis both resulted in azoospermia 38,39 together with hypogonadism in one case in (testosterone 145 ng/dL) 39 . Hallak et al also reported two cases of TSS in single testes with a decrease in testosterone in one patient in their series to 195 ng/dL 34 .…”
Section: Fertility and Endocrine Function Following Partial Orchidectomymentioning
confidence: 94%
“…Two case reports of PO in a solitary testis both resulted in azoospermia 38,39 together with hypogonadism in one case in (testosterone 145 ng/dL) 39 . Hallak et al also reported two cases of TSS in single testes with a decrease in testosterone in one patient in their series to 195 ng/dL 34 .…”
Section: Fertility and Endocrine Function Following Partial Orchidectomymentioning
confidence: 94%